Aetiology of gastroschisis: a prospective case control study to investigate the role of body mass index, alcohol and nutrition. (7th June 2011) - Paranjothy, S; Broughton, H; Evans, A; Huddart, S; Drayton, M; Rankin, J; Jefferson, R; Draper, E; Cameron, A; Palmer, S R
Abstract : Study aim: To investigate the role of diet, cigarette smoking and alcohol consumption and body mass index (BMI) in the aetiology of gastroschisis. Methods: Study design: Case-control study. Cases were identified following the 18–20 weeks anomaly USS, and three controls matched for maternal age and booking centre were sought per case. Interviews used a standard questionnaire. Particular emphasis was placed on establishing in depth and detail exposures that occurred during the first trimester. Data were analysed using Conditional Logistic Regression to describe the associations between exposure variables and gastroschisis. Main results: From July 2007 to February 2010, 124 gastroschisis cases were identified by collaborating centres. 73% of cases (n=91) and 70% of controls (n=216) were recruited. In the multivariable model that included social class of the mother, cigarette smoking, alcohol consumption, BMI and fruit and vegetable consumption, cigarette smoking (cigarettes per day adjusted OR 2.6 95%CI 1.0, 6.7) and routine and manual occupations (adjusted OR 4.6 95%CI 1.5, 14.3) were independent risk factors while obesity and higher consumption of fruit and vegetables (≤28 portions per week) had strong independent protective effect (adjusted OR 0.2 95%CI 0.1, 0.7 for obesity and 0.1 95%CI 0.03, 0.5 for fruit and vegetables). Conclusion: The increased risk associated with cigarette smoking during the first trimester, and protective effect associated with higher BMI is consistent with previous studies. The new finding of the protective effect of consuming higher portions of fruit and vegetables has implications for dietary advice to pregnant women.